Experimental investigations on electrical-insulation performance of Al2O3 coatings for high temperature PbLi liquid metal applications. (March 2022) - Saraswat, Abhishek; Sasmal, Chandrasekhar; Prajapati, Ashokkumar; Bhattacharyay, Rajendraprasad; Chaudhuri, Paritosh; Gedupudi, Sateesh
Highlights: AlPO4 bonded alumina coating on SS-316L substrates has been investigated for electrical-insulation within liquid metal lead–lithium for duration upto 1360 h. Coating application requires low temperature heat-treatment and provides volumetric electrical-resistivity between 10 9 –10 11 Ω-cm within liquid metal at a bulk temperature of 300 °C-400 °C. A novel measurement technique is applied to measure in-situ insulation resistance of the coating within liquid lead–lithium environment. Metallurgical analyses corroborate liquid metal ingress depth restricted to 20 µm. Abstract: Electrical-insulating coatings are of great importance for applications in liquid metal breeder/coolant based systems relevant to nuclear fusion power plants. In specific to lead–lithium eutectic (Pb-16Li), a candidate breeder material, such coatings are being actively investigated worldwide for their criticality in addressing various functionalities including, but not limited to, reduction in Magneto-Hydro Dynamics (MHD) pressure drop, corrosion resistance to structural materials and development of specific diagnostics, like two-phase detection techniques. For such applications, a candidate coating must be demonstrated for its compatibility with corrosive media, endurance towards high operational temperatures and integrity of electrical-insulation over long operational durations without substantial degradation. Further, quantitative performance assessment of coated substrates within PbLi environment over long operational durations is rendered difficult due to scarcity of relevant in-situ insulation resistance data. To address this shortfall, a preliminary experimental study was performed at Institute for Plasma research (IPR) towards application of AlPO4 bonded high-purity alumina (Al2 O3 ) coatings on SS-316L substrates and further rigorous validation in static PbLi environment. The adopted coating process required a low temperature heat treatment (<430 °C) and could yield average coating thicknesses in the range of ∼ 100 µm – 500 µm. Coated samples were validated for their electrical-insulation integrity in static PbLi over two test campaigns for continuous durations of over 700 h and 1360 h, including thermal cycling, at operational temperature in the range of 300 °C-400 °C. Volumetric electrical-resistivity, estimated through high-voltage insulation resistance measurements at relevant temperatures, remained of the order of 10 9 -10 11 Ω-cm without significant degradation. In-situ estimations of thermal derating factors establish good electrical-insulation characteristics after long term exposure to liquid PbLi. This paper presents details of utilized coating application methods, coating thickness estimations, liquid metal test set-up, insulation performance and critical observations from SEM/EDX and XRD analysis on the tested samples.